Comparative Genomic Analysis of Two Serotype 1/2b Listeria monocytogenes Isolates from Analogous Environmental Niches Demonstrates the Influence of Hypervariable Hotspots in Defining Pathogenesis - Casey, Aidan; Jordan, Kieran; Coffey, Aidan; Fox, Edward M.; McAuliffe, Olivia (Frontiers in Nutrition, 2016)
The vast majority of clinical human listeriosis cases are caused by serotype 1/2a, 1/2b, 1/2c and 4b isolates of Listeria monocytogenes. The ability of L. monocytogenes to establish a systemic listeriosis infection within a host organism relies on a combination of genes that are involved in cell recognition, internalization, evasion of host defences and in vitro survival and growth. Recently, whole genome sequencing and comparative genomic analysis have proven to be powerful tools for the identification of these virulence-associated genes in L. monocytogenes. In this study, two serotype 1/2b strains of L. monocytogenes with analogous isolation sources, but differing infection abilities, were subjected to comparative genomic analysis. The results from this comparison highlight the importance of accessory genes (genes which are not part of the conserved core genome) in L. monocytogenes pathogenesis. In addition, a number of factors which may account for the perceived inability of one of the strains to establish a systemic infection within its host have been identified. These factors include the notable absence of the Listeria pathogenicity island 3 (LIPI-3) and the stress survival islet (SSI-1), of which the latter has been demonstrated to enhance the survival ability of L. monocytogenes during its passage through the host intestinal tract, leading to a higher infection rate. The findings from this research demonstrate the influence of hypervariable hotspots in defining the physiological characteristics of a L. monocytogenes strain, and indicate that the emergence of a non-pathogenic isolate of L. monocytogenes may result from a cumulative loss of functionality rather than by a single isolated genetic event.